Pengaruh Metode Tasmi’ dan Motivasi Menghafal Al-Qur’an Terhadap Kualitas Hafalan Al-Qur’an Santriwati Madrasah Tsanawiyah - Kurnia, Sitti; Safaruddin, Safaruddin; Fitriani, Fitriani (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to test the Influence of the Tasmi' Method and the Motivation to Memorize the Qur'an on the Quality of Al-Qur'an Memorization of MTs Students in Islamic Boarding Schools. This type of research is ex post facto with a quantitative approach. Data collection techniques are tests, questionnaires and documentation. The data analysis technique is carried out by classical assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, then multiple linear regression tests, namely the T test and F test. The results of the study showed that the T test of the tasmi' method (X1) was obtained from T-count of 2,598 with a significant value of 0.017, this shows a significant value smaller than 0.05 (0.05> 0.017) Ttable (2,598> 1.725), it can be said that the hypothesis Ha is accepted and Ho is rejected, which means that there is an influence of the tasmi method (X1) on the quality of Al-Qur'an memorization (Y). The results of the T test of the Motivation to Memorize the Qur'an (X2) contained a t count of -2.380 with a significant value of 0.027 which indicates that the significant value is smaller than 0.05 (0.027 <0.05) ttable (-2.380> 1.725), then it is said that the hypothesis Ha is accepted and Ho is rejected which means that the motivation to memorize the Qur'an (X2) has an effect on the quality of Al-Qur'an memorization (Y). The results of the F Test are that there is an influence of the tasmi method (X1) and the motivation to memorize the Qur'an (X2) on the quality of Al-Qur'an memorization (Y) of female MTs students at the Islamic Boarding School, obtained a value of 0.004 <0.05 with a large influence of 39.4%.